Coral Fish Ecology Syngnathidae as Ecotourism Supporting Power in Blue Lagoon Coastal Waters Karangasem, Bali - Saraswati, Suprabadevi Ayumayasari; Pebriani, Dewa Ayu Angga; Pratama, Kolis (Advances in Tropical Biodiversity and Environmental Sciences; Vol 2 No 2 (2018): ATBESDO - 10.24843/ATBES.2018.v02.i02.p03, 2018)
The Syngnathidae reef fish belongs to the vulnerable category of CITES due to the decrease in its original habitat. This is due to the high activity of predatory and utilization as raw material of traditional medicine. This study aims to study the ecological conditions including the distribution and abundance of reef fish Syngnathidae in the waters of the Blue Lagoon Karangasem waters and study the physical condition of its aquatic chemistry. This research was conducted from August to October 2017. The determination of research station was done based on Purposive sampling methods. For data retrieval of the Syngnathidae reef fish using square squares method with size 10x10 m in each sampling location. The result of this research is the emergence of species of reef fish Syngnathidae ranged from 1-4 individual at each location of observation. The results show that the ecological condition of the Syngnathidae reef fish in the Blue Lagoon coastal waters is of concern, this refers to the distribution and abundance of the limited reef fish Syngnathidae in its distribution. On the other hand, analysis of physical chemistry data shows that the condition of Blue Lagoon coastal waters tends to be stable. Measurement of water physics-chemical parameters obtained result of temperature measurement range 28-29 o C, salinity 27-29 ppt, pH 7.08-7,89 and DO 7-7,75 mg/l. The result of physicochemical parameter measurement is related to the quality standard of Kep.Men.LH No.51 about the quality of the waters for marine biota was good for the existence of Syngnathidae reef fish. In general, the aquatic chemical physics conditions have a significant influence on the emergence of reef fish Syngnathidae found in stations 1 and III but not found in station II located in the middle of the waters between stations I and III.